Prevalence of Overweight and Obesity in 2-6 Years Old Children from a Kindergarten - Pinto,Alex (2016)
Introduction: Childhood overweight and obesity is a worldwide concern. Physical activity and food patterns are main factors associated with overweight at preschool age. Centro de Apoio Social de Mozelos is a kindergarten where food habits have been supervised by a nutritionist and where physical activity is freely offered to all children aged 2 to 6 years old. Objectives: This study aimed to investigate the prevalence of overweight and obesity in children aged 2 to 6 years old. Methodology: A sample of 129 children from Centro de Apoio Social de Mozelos (3.7±1.2 years old) was studied. Anthropometric measurements were performed in children and parents. A questionnaire for sample characterization was answered by parents. Overweight and obesity were defined using World Health Organization criteria. Results: The global prevalence of overweight and obesity in children was 11.7% (7.8% of overweight; 3.9% of obesity). Overweight and obesity prevalence in parents was 57.8% (40.5% of overweight; 17.3% of obesity). Conclusions: The prevalence of overweight and obesity in parents seems to follow the general Portuguese population. However, results found in children are below our expectations comparing to similar studies. Further longitudinal studies are needed to clearly demonstrate the benefits of a combined nutritional and physical activity management approach in kindergartens like Centro de Apoio Social de Mozelos in the prevention/reduction of overweight and obesity in preschool aged children.